Olfactory sensitivity in mammalian species - Wackermannová, M; Pinc, L; Jebavý, L (Physiological research, 2016)
Olfaction enables most mammalian species to detect and discriminate vast numbers of chemical structures called odorants and pheromones. The perception of such chemical compounds is mediated via two major olfactory systems, the main olfactory system and the vomeronasal system, as well as minor systems, such as the septal organ and the Grueneberg ganglion. Distinct differences exist not only among species but also among individuals in terms of their olfactory sensitivity; however, little is known about the mechanisms that determine these differences. In research on the olfactory sensitivity of mammals, scientists thus depend in most cases on behavioral testing. In this article, we reviewed scientific studies performed on various mammalian species using different methodologies and target chemical substances. Human and non-human primates as well as rodents and dogs are the most frequently studied species. Olfactory threshold studies on other species do not exist with the exception of domestic pigs. Olfactory testing performed on seals, elephants, and bats focused more on discriminative abilities than on sensitivity. An overview of olfactory sensitivity studies as well as olfactory detection ability in most studied mammalian species is presented here, focusing on comparable olfactory detection thresholds. The basics of olfactory perception and olfactory sensitivity factors are also described.
Keywords: lidé; Humans; senzorické prahy; Animals; čichová percepce; zvířata; Sensory Thresholds; Olfactory Perception; Smell; čich